PEMBELAJARAN BERBASIS KECERDASAN ARTIFISIAL DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MURID STUDI ANALISIS DI SDN 2 SELAAWI - Rizki Normayunita; Ratna Dewi; Nina Herlina; Waska Warta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the implementation of artificial intelligence-based learning management in improving students' critical thinking skills at SDN 2 Selaawi, Maniis District, Purwakarta Regency. This study used a descriptive qualitative approach, involving the principal, teachers, school operators, and students as informants. Data collection was conducted through observation, interviews, and documentation studies. After data collection, the data were analyzed interactively through data reduction, data presentation, and conclusion drawing. The results indicate that artificial intelligence-based learning at SDN 2 Selaawi has been implemented based on four management functions: planning, organizing, implementing, and evaluating or monitoring, but has not been optimal. The planning aspect focuses on targeting students' critical thinking competencies, organizing ICT resources, implementing through the use of adaptive platforms, and process-based evaluation. Field findings indicate that the use of artificial intelligence can improve students' critical thinking skills in evaluating information and formulating solutions independently. Although still hampered by teachers' digital competence and stable connectivity, school management commitment is a key factor in the success of this program. The conclusion of this study confirms that effective management of the use of artificial intelligence can create an interactive learning ecosystem and stimulate critical thinking skills in elementary school students.